International criminal responsibility of the State and transnational organizations for environmental crimes - ali, Aissa; abdelssadouk, kheira (Revue jurisprudence, 2019)
Environmental crimes are considered the most of time as a serious crimes against the international community in all its components and most frequently in cases of war and peace. In view of this seriousness, the international community seeks to adopt principles and legal rules that oblige the people of the international community to respect and not to violate them under sanctions that differ according to the offense committed. Since states are primarily responsible for any act that violates international norms, their liability for civil environmental crimes is no longer an obstacle to the application of the law, which raises the question of the international criminal responsibility of States and transnational organizations with the provisions of contemporary international law, Through the activation of international mechanisms and organs of the United Nations in the exercise of its functions.